Returns to education and occupations for Canadian Aboriginal people. Issue 12 (4th December 2017) - Fan, Lida; Brownlee, Keith; Habibov, Nazim N.; Neckoway, Raymond
Abstract : Purpose: The purpose of this paper is twofold. First, drawing on a unique data set, the authors estimate the returns to education for Canadian Aboriginal people. Second, the authors explore the relationship between occupation and the economic well-being, measured as income, of Aboriginal people in an effort to provide a better understanding of the causes of income gaps for Aboriginal people. Design/methodology/approach: The data used in this study is the Public Use Microdata File of Aboriginal People's Survey, 2012. An ordered logit model is used to estimate the key determinants for income groups. Then the marginal effects of each variable, for the probability of being in each category of the outcomes, are derived. Findings: All the explanatory variables, including demographic, educational and occupational variables, appeared statistically significant with predicted signs. These results confirmed relationships between income level and education and occupations. Research limitations/implications: The data limitation of income, as a categorical variable prevents the precise estimation of the contributions of the dependent variables in dollar amount. Social implications: In order to substantially improve the Aboriginal people's market performance, it is important to emphasise the quality of their education and whether their areas of study could lead them to high-skilled occupations. Originality/value: Attention is paid to the types of human capital rather than the general term of education.